Numerical Study of the Behaviour of a Circular Footing on a Layered Granular Soil Under Vertical and Inclined Loading - Singh, Surja Pratap; Roy, Amrit Kumar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper aims to study the behaviour of a circular footing resting on two granular layers, i.e., a dense sand layer resting on loose sand strata, subjected to a vertical and an inclined loading using the finite element (FE) software PLAXIS-3D. The Mohr-Coulomb criterion is employed for the analysis of the model, in which two parameters are considered to vary significantly; (1) thickness of the top layer (dense layer) and (2) friction angle of both the layers.
Keywords: circular footing; layered granular soil; numerical modelling; model test; fundament kołowy; grunt ziarnisty; podłoże warstwowe; modelowanie numeryczne; test modelowy